Evaluation of serum markers in the LRF CLL4 trial: β2-microglobulin but not serum free light chains, is an independent marker of overall survival. Issue 10 (2nd October 2016) - Pratt, Guy; Thomas, Peter; Marden, Nicola; Alexander, Denis; Davis, Zadie; Hussey, David; Parry, Helen; Harding, Stephen; Catovsky, Daniel; Begley, Joe; Oscier, David
Abstract: Chronic lymphocytic leukemia (CLL) is characterized by heterogeneous clinical behavior and there is a need for improved biomarkers. The current study evaluated the prognostic significance of serum free light chains (sFLC, kappa, and lambda) and other serum markers (bar, serum thymidine kinase (sTK), soluble CD23, and LDH) together with established biomarkers in 289 patients enrolled into the LRF CLL4 trial. In a multivariable analysis of serum markers alone, higher big and kappa light chains were statistically significant in predicting disease progression and higher blg, and sTK in predicting mortality. In multivariable analysis for overall survival the following were independently significant: β2 M levels, immunoglobulin gene ( IGHV ) mutational status (>98% homology), age, 17p13 deletions (>10%), and CD38 expression. β2 M is the only serum marker that retained clear independent value as a biomarker in the LRF CLL4 trial and remains powerfully prognostic requiring evaluation in any future method of risk stratifying patients.